Detransition, baby eaudiobook A novel. - Peters, Torrey (Random House Audio, 2021)
NATIONAL BESTSELLER • The lives of three women—transgender and cisgender—collide after an unexpected pregnancy forces them to confront their deepest desires in “one of the most celebrated novels of the year” ( Time ) “Reading this novel is like holding a live wire in your hand.”— Vulture One of the New York Times ’s 100 Best Books of the 21st Century Named one of the Best Books of the Year by more than twenty publications, including The New York Times Book Review, Entertainment Weekly, NPR, Time , Vogue , Esquire , Vulture , and Autostraddle PEN/Hemingway Award Winner • Finalist for the Lambda Literary Award, the National Book Critics Circle Award, and the Gotham Book Prize • Longlisted for The Women’s Prize • Roxane Gay’s Audacious Book Club Pick • New York Times Editors’ Choice Reese almost had it all: a loving relationship with Amy, an apartment in New York City, a job she didn't hate. She had scraped together what previous generations of trans women could only dream of: a life of mundane, bourgeois comforts. The only thing missing was a child. But then her girlfriend, Amy, detransitioned and became Ames, and everything fell apart. Now Reese is caught in a self-destructive pattern: avoiding her loneliness by sleeping with married men. Ames isn't happy either. He thought detransitioning to live as a man would make life easier, but that decision cost him his relationship with Reese—and losing her meant losing his only family. Even though their romance is over, he longs to find a way back to her. When Ames's boss and lover, Katrina, reveals that she's pregnant with his baby—and that she's not sure whether she wants to keep it—Ames wonders if this is the chance he's been waiting for. Could the three of them form some kind of unconventional family—and raise the baby together? This provocative debut is about what happens at the emotional, messy, vulnerable corners of womanhood that platitudes and good intentions can't reach. Torrey Peters brilliantly and fearlessly navigates the most dangerous taboos around gender, sex, and relationships, gifting us a thrillingly original, witty, and deeply moving novel.